Effects of sex steroid hormones on acylation stimulating protein (ASP) and related gene expression - Al Riyami, Bashair (2018)
Metabolic complications of obesity are mainly linked to body fat distribution. Since body fat distribution is sex-linked, understanding the role of sex hormones in body fat distribution and storage is important. The acylation stimulating protein (ASP) is a novel lipogenic factor that is suggested to be influenced by hormonal changes. The aim of the present study was to investigate the effect of sex steroid hormones on ASP production and related gene expression, by using adipose tissue explants isolated from ovariectomized rats and the 3T3-L1 cell line generated from mouse embryonic fibroblast cells. In ex vivo studies, 3-way ANOVA analysis showed an effect of hormones, fat depots and chylomicrons interactions on ASP production (p=0.005). Further analysis demonstrated that progesterone and estrogen (P&E) treatment stimulated ASP production (p=0.006) in comparison to estrogen group in subcutaneous adipose tissue explants. In the presence of chylomicrons, visceral adipose tissue explants incubated with P&E showed increased ASP secretion by 54% (p=0.003). The same treatment led to a significant reduction of ASP concentration in subcutaneous explant media (32% lower, P=0.03). C5L2 protein expression were more affected by hormone and chylomicrons interaction (p=0.025). The expression of C5L2 protein increased significantly by P&E treatment (p=0.04) in comparison to the control group in subcutaneous tissue explants. Fat depots and chylomicrons interaction showed a significant effects on effect on ASP’s precursors C3 (p=0.003), factor B (p=0.009) and adipsin (p=0.001) mRNA expressions. DGAT1 have shown to be influenced by hormone and chylomicrons interactions (p=0.3) with no interaction effect on LPL mRNA expression. Using 3T3-L1 cells, high doses of progesterone in the presence of estrogen significantly induced ASP production (p< 0.001). C5L2 protein expression increased in dose-dependent manner with progesterone or estrogen treatments. Treatment of 3T3-L1 adipocyte cells with P&E and chylomicrons had no effect on ASP production. Estrogen receptors (ERs) blockade increased the gene expression of C5L2 and PLC significantly by 5-fold. In summary, female steroid hormones (P&E) may regulate fat distribution through their effects on ASP and C5L2 in subcutaneous adipose tissue. Chylomicrons modulated the ASP responses to P&E treatment in this tissue. P&E interaction with ASP was proven to be regulated through their receptors (PR and ERs) in 3T3-L1 adipocytes. These results demonstrated an important role of female sex steroid in fat distribution and adipocyte lipid metabolism by mediating ASP- C5L2 pathway. Therefore ASP is an important lipogenic factor that, under normal female hormonal states, may reduce the metabolic health risk in women.